Dose dependent effects of oral progesterone on the oestrogenised postmenopausal endometrium. Issue 6401 (29th October 1983) - Lane, G; Siddle, N C; Ryder, T A; Pryse-Davies, J; King, R J; Whitehead, M I
Abstract : Oral progesterone 100, 200, or 300 mg daily was given for the first 10 days of each calendar month to postmenopausal women also receiving conjugated oestrogens 1.25 mg daily continuously. Endometrial biopsy specimens were taken on the sixth day of the third or subsequent cycle of combined treatment for histological, ultrastructural, and biochemical evaluation. Secretory histological changes were induced within the endometrium in a dose dependent manner, as were progesterone sensitive ultrastructural features such as nucleolar channel systems, giant mitochondria, and subnuclear accumulations of glycogen. Dose response relations were also observed for suppression of DNA synthesis and nuclear oestrogen receptor, and for induction of the activities of oestradiol and isocitric dehydrogenases. Progesterone administered by mouth clearly provokes an end organ response within the endometrium. Suboptimal effects were observed with the lower doses but progesterone 300 mg daily achieved responses approaching and within the physiological range. This dose may therefore be effective as an alternative to synthetic progestogens for therapeutic purposes.